Η6‐Arene(halogenidoaluminato)lanthanoid(III) Complexes: Synthesis, Characterization and Catalytic Activity for Isoprene Polymerization. Issue 7 (24th January 2022) - Hossain, Md Elius; Guo, Zhifang; Wang, Jun; Deacon, Glen B.; Junk, Peter C.; Diether, Dominic; Anwander, Reiner
Abstract: η 6 ‐Arene(iodido‐/bromido‐aluminato)lanthanoid(III) complexes, [Ln(η 6 ‐C6 H5 Me)(AlI4 )3 ] [Ln=La (1 ), Ce (2 ), Nd (3 ), (Gd) (4 ); C6 H5 Me=toluene], [Ln(η 6 ‐C6 H3 Me3 ‐1, 3, 5)(AlI4 )3 ] [Ln=La (5 ), Ce (6 ), Pr (7 ), Nd (8 ), Sm (9 ), Gd (10 ); C6 H3 Me3 ‐1, 3, 5=mesitylene], and [Ln(η 6 ‐C6 H5 Me)(AlBr4 )3 ] [Ln=La (11 ), Nd (12 ), Sm (13 )] were prepared by reactions of aluminium triiodide or aluminium tribromide with the corresponding lanthanoid metals and 1, 2‐diiodoethane or 1, 2‐dibromoethane in an arene (toluene or mesitylene) solution (molar ratio : 6 : 2 : 3). The first X‐ray crystal structures of arene(iodidoaluminato)lanthanoid(III) complexes are reported. The lanthanoid atom is coordinated by an η 6 ‐arene and three chelating κ(I, I′)‐tetraiodidoaluminato ligands. The tetrabromidoaluminate complexes have similar structures. The precatalyst 3 was treated with AlR3 (R=Me or i Bu) to give [Nd(η 6 ‐C6 H5 Me)(AlI3 R)3 ] species in situ, which were then tested for catalytic activity towards isoprene polymerization. Although the resulting polyisoprene had a desirable high cis‐ 1, 4 content, the catalyst performance was well below known best performing systems and indicates that iodidoaluminates are the least favorable of the halogenidoaluminatolanthanoid(III) complexes. Abstract : Lanthanoid (III) iodido‐/bromido‐aluminato η 6 ‐arene complexes, [Ln(η 6 ‐C6 H5 Me)(AlI4 )3 ], [Ln(η 6 ‐C6 H3 Me3 ‐1, 3, 5)(AlI4 )3 ], and [Ln(η 6 ‐C6 H5 Me)(AlBr4 )3 were prepared and structurally characterized. The catalytic activity of [Nd(η 6 ‐C6 H5 Me)(AlI4 )3 ] towards isoprene polymerization has also been investigated.